2000
DOI: 10.2165/00019053-200018050-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of an Adult Outpatient Parenteral Antibiotic Therapy (OPAT) Programme

Abstract: This analysis supports the premise that an adult OPAT programme can substantially reduce healthcare costs in the Canadian healthcare setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 9 publications
1
56
0
2
Order By: Relevance
“…Today, indications for OPAT programs, which are successfully used, differ among countries [23,24] . In a study which analyzed the cost of OPAT in adult patients in a tertiary training hospital in Canada between 1995 and 1998, different parenteral antibiotics were administered for different types of infections, such as bone and joint, skin and soft tissue, endocarditis and others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, indications for OPAT programs, which are successfully used, differ among countries [23,24] . In a study which analyzed the cost of OPAT in adult patients in a tertiary training hospital in Canada between 1995 and 1998, different parenteral antibiotics were administered for different types of infections, such as bone and joint, skin and soft tissue, endocarditis and others.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that OPAT programme provided an economically attractive alternative to continued hospitalization for selected adult patients with infections requiring parenteral antimicrobial treatment. Also from the hospital perspective, the cost of therapy through the OPAT programme was approximately 13% of the cost estimated if the patient was to continue to be managed in hospital settings [23] . In another study from UK, clinical efficacy and cost-effectiveness of OPAT in 334 episodes (skin and soft tissue infections, cardiovascular infections, central nervous system infections, genito-urinary infections, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…OPAT has demonstrated costeffectiveness benefits when compared to a full in-hospital IV antibiotic treatment course [2]. A recent analysis of a 334-person cohort in the UK estimated a yearly cost of approximately £300,000 (including pre-clinical set-up costs), whereas the minimum theoretical in-patient cost was more than three times higher at £1,005,676 [3].…”
Section: Abstract R é S U M émentioning
confidence: 99%
“…[1][2][3] The increasing use of OPAT prompted the first Infectious Diseases Society of America (IDSA) practice guideline for community-based parenteral anti-infective therapy in 1997, which was recently updated in 2004. 4,5 We found no clinical data on the validity or reliability of documenting response to therapy despite many recent published reviews on the topic of SSTIs.…”
Section: Ré Sumémentioning
confidence: 99%